Doping effect on magnetic properties of high-temperature multiferroic compound YBaCuFeO5 - Yukio Yasui; Shiori Kihara; Kota Ikeda; Taichi Banshodani (AIP Advances, 2024)
We have investigated the impurity effects on magnetic properties for the oxygen-deficiency ordered perovskite YBaCuFeO5, which has multiferroic phenomenon at TN2 = 319 K. The measurements of the magnetic susceptibility χ have been carried out for the polycrystalline samples of YBaCu1-xMxFeO5 (M = Ni, Mn, and Zn), where the Cu2+ spins (S = 1/2) are partially substituted by the nonmagnetic and magnetic ions. From anomalies of the temperature dependence of χ, the doping concentration dependences of the magnetic transition temperatures such as TN1 and TN2, were determined. With increasing the doping concentration for YBaCu1-xMxFeO5 (M = Ni, Mn, and Zn), the value of TN1 decreases, and that of TN2 increases, and two magnetic transitions become one at x = xc. In the doping region of x > xc, the magnetic behaviors of the magnetic ions doped systems are different from that of the nonmagnetic one. In particular, we found that two magnetic transitions newly appear for the Ni- and Mn-doped systems in the region of x > xc. Based on the obtained results, we discussed the physics of impurity effects on the magnetic transitions for the high-temperature multiferroic compound YBaCuFeO5.